آليات تسوية منازعات الصفقات العمومية (في ظل أحكام المرسوم الرئاسي:15/247) - حمايتي, صباح (unuversity of eloued- جامعة الوادي, 2018)
لقد منح المشرع الجزائري مكانة خاصة للصفقات العمومية لما لها أهمية كبرى على الاقتصاد الوطني ، وهذا ما لمسناه من خلال سلسلة التعديلات المتتالية لهذا القانون، نتيجة التعقيدات التي تطرح في الجانب العملي وخاصة ما تعلق بالمنازعات التي تثار في مختلف مراحل إبرام الصفقة. خلق المرسوم الجديد المتعلق بتنظيم الصفقات العمومية نوع من الإحاطة القانونية لجميع الإشكاليات من خلال التنوع في الآليات، ومنح الاولوية لتسوية الودية للنزاعات باعتبارها الآلية الأنجع من أجل التعجيل في تنفيذ المشاريع أمام بطئ إجراءات التقاضي. ذلك من خلال تبنى الطعون المختلفة سواء الإدارية أو القضائية في المراحل التمهيدية للإبرام، وقيد الأطراف المتعاقدة بإلزامية اللجوء للتسوية الودية للنزاع في مرحلة التنفيذ معتمدا على آليات كالصلح، التحكيم واستحداث لجان خاصة بالتسوية الودية للنزاع.The Algerian legislator has given special status to public deals because they are of its of great importance to the national economy , as we have seen through successive series of amendments to this law ,due to the complexities in the practical aspect , especially concerning to the litigations that arise at different stages of conclusion of the deal . The new decree on the regulation of public transactions created a kind of legal briefing of all problems , through a variety of mechanisms and prioritizing the amicable settlement of litigations as the most effective mechanism in order to expedite the implementation of projects before the slow pace of litigation. Through the adoption of various appeals ,whether administrative or judicial in the preliminary stages of the conclusion ,and the restriction of the contracting parties to the mandatory resort to a friendly settlement of the conflict in the implementation phase ,based on mechanisms such as reconciliation , arbitration and the establishment of committees for the friendly settlement of the dispute.
The mechanisms of settlement of public deals disputes
مقال
Keywords: الطعون الإدارية ؛الصلح ؛ التحكيم ؛ لجنة ؛التسوية الودية ؛ الطعون القضائية.; Administrative appeals ; reconciliation ; arbitration friendly Settlement Committee; Judicial appeals.